Property valuation in an economic context - Wyatt, Peter, 1968- (Oxford ; Malden, MA : Blackwell Pub., 2007)
This book provides a single text for postgraduate study of valuation on real estate courses. After a general introduction to the property market and the economic ideas that underlie valuation, it introduces the theory of valuation as a set of analysis techniques for identifying and understanding market signals in a financial context. The final section of the book, describes the three categories of market players who rely on valuation advice - the developer, investor and occupier.; 'all in one' text for postgraduate study of valuation on real estate courses.? sets valuation in its business fin.
Property Valuation : in an economic context; Contents; Preface; Acknowledgements; 1. The Economics of Property Value; 2. Property Valuation Principles; 3. Valuation Methods; 4. Property Occupation Valuation; 5. Property Investment Valuation; 6. Property Development Valuation; 7. Property Appraisal; Glossary; Index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Commercial real estate -- Valuation -- Great Britain; Real estate investment -- Great Britain; Immobilier d'entreprise -- Grande-Bretagne; Immeubles -- Investissements -- Grande-Bretagne.; BUSINESS & ECONOMICS -- Real Estate -- Commercial; Commercial real estate -- Valuation; Real estate investment; Great Britain